Patient satisfaction after total hip arthroplasty: Influencing factors - Shao, Zhuce; Bi, Shuxiong (Frontiers in Surgery, 2023)
It is reported that the dissatisfaction rate after primary total hip replacement (THA) is between 7% and 20%. Patient satisfaction has already become a public health problem that puzzles the world, and it is a problem to be solved that cannot be ignored in the development of global public health. The purpose of this paper is to conduct a narrative review of the literature to answer the following questions: what are the main factors leading to high patient satisfaction or dissatisfaction after THA? The literature on patient satisfaction after THA was reviewed. As far as we know, there is no such a detailed and timely overview of THA satisfaction as this article, and the purpose articles we use search engines to search are all RCT (Randomized Controlled Trial) type works, excluding cross-sectional studies and other experiments with low evidence level, so the quality of this article is high. The search engines used are MEDLINE (PubMed) and EMBASE. The keywords used are "THA" and "satisfaction". The main preoperative, perioperative and postoperative factors that affect patient satisfaction are summarized in detail below.